2017
DOI: 10.3390/ijms18020238
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling Identifies Characterization of Non-Obstructive Azoospermic Men

Abstract: Male infertility is considered a common health problem, and non-obstructive azoospermia with unclear pathogenesis is one of the most challenging tasks for clinicians. The objective of this study was to investigate the differential serum metabolic pattern in non-obstructive azoospermic men and to determine potential biomarkers related to spermatogenic dysfunction. Serum samples from patients with non-obstructive azoospermia (n = 22) and healthy controls (n = 31) were examined using high-performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
22
0
1
Order By: Relevance
“…Spermatozoa can be affected by ROS hazardously through its damaging effects on sperm membrane lipids, mitochondrial function and DNA integrity. Infertile men with defective spermatogenesis, as in NOA, were found to have inherent metabolic stresses and higher levels of testicular oxidative stress (Rahbar et al., 2017; Zhang et al., 2017). Induction of further OS for testicular spermatozoa could theoretically affect the outcomes of ICSI using these spermatozoa (Ghaleno et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Spermatozoa can be affected by ROS hazardously through its damaging effects on sperm membrane lipids, mitochondrial function and DNA integrity. Infertile men with defective spermatogenesis, as in NOA, were found to have inherent metabolic stresses and higher levels of testicular oxidative stress (Rahbar et al., 2017; Zhang et al., 2017). Induction of further OS for testicular spermatozoa could theoretically affect the outcomes of ICSI using these spermatozoa (Ghaleno et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FSH levels and sperm count do not influence the balance of the AA concentrations and may not be correlated to spermatogenic function in infertile men. In a previous study, investigating serum samples from non-obstructive azoospermic men, various metabolic pathways, but not those associated with AAs, were shown to be disrupted, suggesting the involvement of serum metabolic disorders in the pathogenesis of male infertility (19).…”
Section: Discussionmentioning
confidence: 88%
“…Considering the important roles of AAs in a wide variety of pathophysiological events, we evaluated our findings, focusing only on men with either normospermia or oligozoospermia, and found significantly lower levels of alanine and tryptophan in men with lower motility rates, and lower levels of aspartic acid and glutamic acid in men with higher abnormal morphology rates. To date, a number of studies have reported the effects of these four AAs on sperm function (8,11,14,15,(19)(20)(21)(22)(23)(24). For example, in vitro motility, longevity, and in vivo fertility were enhanced in bull spermatozoa by tryptophan supplementation (11), while oral administration of aspartic acid resulted in the improvement of sperm quality and fertility using a rooster model (20).…”
Section: Discussionmentioning
confidence: 99%
“…A differentiated serum metabolomic profiling has also been described in non-obstructive azoospermic men in comparison to healthy control subjects. Results identified 24 metabolites involved in crucial steps for spermatogenesis, such as energy production, oxidative stress and cell apoptosis ( Zhang et al ., 2017 ).…”
Section: Resultsmentioning
confidence: 99%